Species diversity and abundance of scorpions in Ahvaz city, Southwest Iran - NAHID JALILI SHAH MANSOURI; Kamran Akbarzadeh; ELHAM JAHANIFARD; BABAK VAZIRIANZADEH; Javad Rafinejad (Society for Indonesian Biodiversity, 2021)
Abstract. Mansouri NJS, Akbarzadeh K, Jahanifard E, Vazirianzadeh B, Rafinejad J. 2021. Species diversity and abundance of scorpions in Ahvaz city, Southwest Iran. Biodiversitas 22: 763-768. Arthropods are one of the most important and diverse phyla of the animal kingdom. This phylum includes several classes of insects and arachnids, which are of medical and veterinary importance. Scorpions are at the top of the group of venomous arthropods in terms of having venomous bites and causing death. Scorpions live mainly in tropical and subtropical regions of the world and therefore have higher diversity and richness in these regions. This study aimed to investigate the biodiversity and abundance of scorpions in Ahvaz city, Khuzestan province, Iran. It has the highest species diversity and species richness in Iranian scorpions. Scorpions were collected from five regions in Ahvaz using various methods. In total 237 scorpions were collected and identified. They belonged to two families, seven genera and seven species: Mesobuthus eupeus (65%), Hemiscorpius lepturus (23.2%), Androctonus crassicauda (3.8%), Compsobuthus rugosulus (3.4%), Orthochirus zagrosensis (2.5%), Apistobuthus susanae (1.7%), Buthacus macrocentrus (0.4%). Except for H. lepturus (Hemiscorpiidae), other species belonged to the Buthidae family. That all of them were non-burrowing. M. eupeus was the dominant species diversity analysis indicated higher species richness and species diversity for summer (Margalef = 1.07; Shannon = 1.55). Logistic regression analysis showed that the variables of geographical location, humidity, and temperature had a significant relationship with the abundance of scorpion species, while height had no statistically significant.